Melanocortin-4 Receptor (MC4R) gene polymorphism and its effect on growth traits in Madura cattle - Prihandini, P. W.; Sumadi, S.; Suparta, G.; Maharani, D. (Journal of the Indonesian Tropical Animal Agriculture, 2019)
Melanocortin-4 receptor (MC4R) gene has an important role in the regulation of feed intake and energy balance control. The objective of this study was to identify the single nucleotide polymorphisms (SNPs) of MC4R gene and their association with growth traits in Madura cattle. A total of 198 calves were used in this study.Forward primer: 5’-GTCGGGCGTCTTGTTCATC-3’and reverse primer: 5’-GCTTGTGTTTAGCATCGCGT-3’ were used to amplify approximately 493 bp of MC4R gene. The results showed that two SNPs, g.1133C>G and g.1108C>T were identified by direct sequencing. The PCR-RFLP method was performed to genotype all individuals studied based on SNP g.1133C>G, and its SNP was significantly associated with shoulder height (SH) at yearling age (P<0.05). Animals with GG genotype had a higher SH (110.35±6.40cm) than those with CC (102.00±8.00 cm) and CG genotype (105.96±6.23 cm). The SNP g.1133 C>G changed amino acid from valine to leucine. In conclusion, the SNP g.1133C>G of the MC4R gene may be used as a marker-assisted selection for SH trait in Madura cattle.